(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2019)
Background: The current study was designed to investigate the safety and efficacy of oral clonidine aspreanesthetic medication on preoperative sedation, analgesia and hemodynamic stability in patientsundergoing gynaecological laparotomy. Method: In a prospective, randomized, double-blind, controlled study sixty adult patients of ASA physicalstatus I & II aged 18-40 yrs, undergoing gynaecological laparotomy received placebo (n=30), clonidine 2-2.5mcg/kg (n=30).These drugs were administered 105 min before the estimated time of induction ofanesthesia. Heart rate & arterial pressure were recorded prior to induction, 5 min intervally upto 20 minin peroperative time and 2 hour intervally upto6 hours in postoperative period. In the Group-A (clonidine2-2.5mcg/kg) mean heart rate ranged from73.80 ±8.69 to 71.45±5.80, while it ranged between 104.40±9.44to 89.65±5.20 in the Group-B. Systolic blood pressure in Group-A (low dose clonidine) was 113.00±7.32,and in Group-B (placebo) was115.00±5.84 where p=0.024. Diastolic blood pressure of Group-A (low doseclonidine) was 76.15±5.29, and in Group-B (placebo) was 73.65±4.23. Preoperative sleepiness was assessedby both nurse and anesthesiologist and postoperative pain was assessed by a blinded observer using aVAS scale. This study was done in the department of anesthesiology of Apollo Hospitals Dhaka over aperiod of six months. Results: Patients in group A showed significant hemodynamic changes compared to placebo. Five patientsin group A showed marked hypotension and bradycardia and treated accordingly.Group A patientsshowed sleepiness and post op analgesia compared to group B. Conclusion: These data suggest that clonidine (100mcg/kg) as premedication is effective to producepreop sedation, stable hemodynamics and to facilitate postop analgesia with some side effects. JBSA 2019; 32(2): 21-26